Computer systems and software engineering concepts, methodologies, tools, and applications (IGI Global, 2018)
"This book is a comprehensive reference source for the latest scholarly material on trends, techniques, and uses of various technology applications and examines the benefits and challenges of these computational developments. Highlighting a range of pertinent topics such as utility computing, computer security, and information systems applications"--